Automotive computer controlled systems diagnostic tools and techniques - Bonnick, Allan W. M. (Oxford ; Boston : Butterworth-Heinemann, 2001)
'Automotive Computer Controlled Systems' explains the fundamental principles of engineering that lie behind the operation of vehicle electronic systems. Having obtained this knowledge, the reader will be able to make full use of the diagnostic equipment which is currently available. The book builds on the concepts contained in Vehicle Electronic Systems and Fault Diagnosis and gives clear steps to fault diagnosis and subsequent repair of the vehicle's electronic systems. The author discusses electronics only within the context of the vehicle systems under consideration, and thus keeps theory to a minimum. Allan Bonnick has written articles for several transport/vehicle journals and carries out consultancy work for the Institute of Road Transport Engineers. In addition, he has had many years teaching experience and is ideally placed to write this informative guide. * Principles discussed in context avoiding unnecessary theory and maths * Practical step-by-step instructions on fault diagnosis and repair * Liberally illustrated with clear diagrams.
Preface; Common technology; The computer ECM; Self diagnosis and fault codes; Diagnostic tools and equipment; Sensors; Actuators; Diagnostic techniques; Additional technology; Appendices; Index.
Includes index.
Keywords: Automotive computers; Automobiles -- Maintenance and repair; Electronic books